Serum amyloid A protein in the course of infectious mononucleosis - Todorov, Iliyan (Ther Adv Infect Dis, 2019)
BACKGROUND: Serum amyloid A (SAA) protein is a major acute phase protein. Increased concentrations have been reported in many inflammatory diseases. In bacterial infections, high levels correlate with those of C-reactive protein (CRP). In viral infections, where CRP changes are weaker, SAA is of value for establishing early diagnosis, monitoring the severity, and the evolution of the disease. OBJECTIVE: Evaluation of SAA as a marker for diagnosis of infectious mononucleosis, including severe forms. MATERIAL AND METHODS: A total of 31 patients with non-complicated and severe, complicated infectious mononucleosis were examined. SAA and CRP were measured by immuniturbidimetric assays at the day of admission and 4.97 ± 1.35 days later. RESULTS: SAA increases significantly than those in a control group, without correlation with the etiologic agent. It decreases when full recovery appears. In the subgroup of subjects with complications, we observed significant increased SAA when Epstein-Barr virus /EBV/ was the etiologic agent, in the course of bacterial and viral secondary infection. SAA is higher than CRP in non-complicated group. In cases of bacterial superinfections, both increase simultaneously and treatment have to be adapted. Second, serum sample for CRP is normal in patients without full recovery where SAA stay increased. CONCLUSION: In viral infections, high SAA concentrations are indicative for early diagnosis, severe course of the diseases, effect of the treatment, early recovery, and disease outcome. When SAA and CRP increase simultaneously, bacterial co-infection is suspected, and relevant antibiotic treatments have to be initiated.